Validity of an Interactive Functional Reach Test - Galen, Sujay S; Pardo, Vicky; Wyatt, Douglas; Diamond, Andrew; Brodith, Victor; Pavlov, Alex (Games for health, 2015)
Videogaming platforms such as the Microsoft (Redmond, WA) Kinect(®) are increasingly being used in rehabilitation to improve balance performance and mobility. These gaming platforms do not have built-in clinical measures that offer clinically meaningful data. We have now developed software that will enable the Kinect sensor to assess a patient's balance using an interactive functional reach test (I-FRT). The aim of the study was to test the concurrent validity of the I-FRT and to establish the feasibility of implementing the I-FRT in a clinical setting. The concurrent validity of the I-FRT was tested among 20 healthy adults (mean age, 25.8±3.4 years; 14 women). The Functional Reach Test (FRT) was measured simultaneously by both the Kinect sensor using the I-FRT software and the Optotrak Certus(®) 3D motion-capture system (Northern Digital Inc., Waterloo, ON, Canada). The feasibility of implementing the I-FRT in a clinical setting was assessed by performing the I-FRT in 10 participants with mild balance impairments recruited from the outpatient physical therapy clinic (mean age, 55.8±13.5 years; four women) and obtaining their feedback using a NASA Task Load Index (NASA-TLX) questionnaire. There was moderate to good agreement between FRT measures made by the two measurement systems. The greatest agreement between the two measurement system was found with the Kinect sensor placed at a distance of 2.5 m [intraclass correlation coefficient (2,k)=0.786; P<0.001] from the participant. Participants with mild balance impairments whose balance was assessed using the I-FRT software scored their experience favorably by assigning lower scores for the Frustration, Mental Demand, and Temporal Demand subscales on the NASA/TLX questionnaire. FRT measures made using the Kinect sensor I-FRT software provides a valid clinical measure that can be used with the gaming platforms.